Penerapan Pembelajaran PKN untuk Meningkatkan Motivasi Belajar pada Materi Bhineka Tunggal Ika di SD Negeri 01 Koya Tengah Kota Jayapura - Yan Dirk Wabiser; Yurenius B. Makayan (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2022)
This study aims to examine the implementation of Citizenship Education (PKn) learning in increasing students' learning motivation on the Bhinneka Tunggal Ika material at SD Negeri 01 Koya Tengah, Jayapura City. The method used is a qualitative approach with observation, interview, and questionnaire techniques. The results of the study showed a significant increase in students' learning motivation after the implementation of interactive and participatory learning methods. This study is expected to contribute to the development of PKn learning in elementary schools.